Career choices: Adaptation and initial evidence of the Work Volition Scale in Brazil - Fernanda Mendes Pires; Alexsandro Luiz De Andrade (BBR: Brazilian Business Review)
Volition is the individual perception of one’s ability to make decisions and career choices despite constraints by the external environment. It is a relevant concept in the Psychology Working Theory, which highlights the role played by contextual factors, social class, privilege, and freedom of choice in career building. This study’s objective was to adapt the Work Volition Scale to the Brazilian context and find initial validity evidence. The sample was composed of 584 Brazilian workers from different social strata. Multi-group confirmatory factor analysis and analysis of correlations indicated that the three-dimensional internal structure is adequate; invariance was found for sex, subjective social class, and the strategies used to apply the instrument. Furthermore, the results suggest a positive association between volition and job satisfaction, while financial constraints are negatively related to job satisfaction and satisfaction with life. The results contribute to studies on career and provide an instrument to be used in vocational and career counseling and research to support public policy from a more inclusive perspective.